PENGARUH KEPERCAYAAN, EWM DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI LAZADA KOTA LHOKSEUMAWE 2021 - Sutan Febriansyah; Ramadhan Razali; Sri Wahyuni; Teuku Afriliansyah (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2021)
The ipurpose iof ithis istudy iwas ito iexamine ithe ieffect iof itrust, ielectronic iword iof imouth iand ibrand iimage ion ionline ipurchasing idecisions iat iLazada. iThe ipopulation iin ithis istudy iwere iall iLazada iwebsite iusers iin iLhokseumawe iCity, iwhile ithe isample iwas i100 irespondents. iThe isampling itechnique iis iaccidental isampling. iThe itypes iof idata iused iin ithis istudy iare iprimary idata iin ithe iform iof icross isection idata iobtained iby iusing iquestionnaires. iThe imethod iof idata ianalysis iin ithis istudy iis ithe imethod iof imultiple ilinear iregression ianalysis. iThe iresults iof ithe istudy ifound ipartially iand isimultaneously ibrand itrust, ielectronic iword iof imouth iand ibrand iimage ihad ia isignificant ieffect ion ionline ipurchasing idecisions.